Bacteriophage application restores ethanol fermentation characteristics disrupted by Lactobacillusfermentum. Issue 1 (December 2015) - Liu, Mei; Bischoff, Kenneth; Gill, Jason; Mire-Criscione, Miranda; Berry, Joel; Young, Ry; Summer, Elizabeth
Abstract Background Contamination of corn mash by lactic acid bacteria (LAB) reduces the efficiency of the ethanol fermentation process. The industry relies heavily on antibiotics for contamination control and there is a need to develop alternative methods. The goals of this study were to determine the diversity and abundance of bacteria contaminating commercial ethanol fermentations, and to evaluate the potential of anti-LAB bacteriophages in controlling production losses. Results Bacterial populations in 27 corn mash samples collected from nine different commercial plants were determined by pyrosequencing of 16S rRNA amplicons. The results showed that the most abundant bacteria (>50 % of total population) in 24 of the 27 samples included LAB genera such asLactobacillus, Streptococcus, Lactococcus, Weissella, Enterococcus, andPediococcus. Lactobacillus was identified as the most prevalent genus at all fermentation stages in all plants, accounting for between 2.3 and 93.7 % of each population and constituting the major genus (>50 %) in nine samples from five plants and the most abundant genus in five other samples.Lactobacillus species, includingL. delbrueckii, L. fermentum, L. mucosae, andL. reuteri were the most well-represented species. Two bacteriophages that targetL. fermentum strains from ethanol plants, vB_LfeS_EcoSau and vB_LfeM_EcoInf (EcoSau and EcoInf), were isolated and characterized as a siphophage and a myophage, respectively. Analysis of the 31, 703 bp genome of EcoSau revealed its similarity to the P335-like phage group, and the 106, 701 bp genome of phage EcoInf was determined to be a novel phage type despite its distant relationship to the SPO1-like phages. Addition of phages EcoSau and EcoInf toL. fermentum -contaminated corn mash fermentation models restored the yields of ethanol and reduced levels of residual glucose, lactic acid, and acetic acid to that comparable to the infection-free control. Conclusions This study provides detailed insight into the microbiota contaminating commercial ethanol fermentations, and highlights the abundance of LAB, especiallyL. delbrueckii, L. fermentum, L. mucosae, andL. reuteri, in the process. This study suggests that phages with broad coverage of major LAB species can be applied directly to corn mash for antibiotic-free control of contamination in the ethanol fermentation industry.